Development of interactive software (shear force & bending moment) - Cham, Benjamin Hong Mian (Nanyang Technological University, 2020)
Shear forces and bending moments on a beam are hard to calculate without the prior knowledge of solving it. You must first determine if the beam is statically determinate or indeterminate. Finally, you solve it using the forces acting on the beam to find out the shear force and bending moment. You will be able to plot out the graph. With this development of software, it will be able to solve problems that will not require users to have prior knowledge. This allows users to solve problems and understand how different forces acting on the beams will affect the beams in term of shear force and bending moment.